Wireless Algorithms, Systems, and Applications : 10th International Conference, WASA 2015, Qufu, China, August 10-12, 2015, Proceedings - Xu, Kuai.; Zhu, Haojin; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2015)
This book constitutes the proceedings of the 10th International Conference on Wireless Algorithms, Systems, and Applications, WASA 2015, held in Qufu, Shandong, China, in August 2015. The 36 revised full papers presented together with 5 revised short papers and 42 invited papers were carefully reviewed and selected from 133 initial submissions. The papers present current trends, challenges, and state-of-the-art solutions related to various issues in wireless networks. Topics of interests include effective and efficient state-of-the-art algorithm design and analysis, reliable and secure system development and implementations, experimental study and testbed validation, and new application exploration in wireless networks.
Privacy-Preserving Public Auditing Together with Efficient User Revocation in the Mobile Environments -- Multi-proxy Multi-signature Binding Positioning Protocol -- Efficient Network Structure of 5G Mobile Communications -- Optimal Channel Assignment Schemes in Underlay CRNs with Multi-PU and Multi-SU Transmission Pairs -- A Group Bandwidth Reservation Scheme for the Control Channel in IEEE 802.11p/1609 Networks -- k-Perimeter Coverage Evaluation and Deployment in Wireless Sensor Networks -- Modeling Flu Trends with Real-Time Geo-tagged Twitter Data Streams -- Radio Signal Based Device-Free Velocity Recognition -- Minimum-Cost Information Dissemination in Social Networks -- Finding Overlapping Communities with Random Walks on Line Graph and Attraction Intensity -- Computing an Optimal Path with the Minimum Number of Distinct Sensors -- ULRAS: Ultra-Lightweight RFID Authentication Scheme for Mobile Device -- Soft Reservation Based Prioritized Access: Towards Performance Enhancement for VoIP over WLANs -- Impact of a Deterministic Delay in the DCA Protocol -- EBRS: Event Based Reputation System for Defensing Multi-source Sybil Attacks in VANET -- iSound: A Smartphone Based Intelligent Sound Fusion System for the Hearing Impaired -- Estimation Based Adaptive ACB Scheme for M2M Communications -- Optimal Power Allocations for Two-Users Spectrum Sharing Cognitive Radio with Interference Limit -- Adaptive Resource Allocation for Anti-money Laundering Based on SMDP -- Infrastructure Deployment and Optimization for Cloud-Radio Access Networks -- A Cluster Head Rotation Cooperative MIMO Scheme for Wireless Sensor Networks -- A Distributed Game-Theoretic Power Control Mechanism for Device-to-Device Communications Underlaying Cellular Network -- A Low Overhead and Stable Clustering Scheme for Crossroads in VANETs -- Online Channel Assignment, Transmission Scheduling, and Transmission Mode Selection in Multi-channel Full-duplex Wireless LANs -- Optimal Preference Detection Based on Golden Section and Genetic Algorithm for Affinity Propagation Clustering -- DRL: A New Mobility Model in Mobile Social Networks -- SGSA: Secure Group Setup and Anonymous Authentication in Platoon-Based Vehicular Cyber-Physical Systems -- A Bidder-Oriented Privacy-Preserving VCG Auction Scheme -- A Secure Multi-unit Sealed First-Price Auction Mechanism -- Flow-Level Performance of Device-to-Device Overlaid OFDM Cellular Networks -- Bernoulli Sampling Based (epsilon, delta)-Approximate Frequency Query in Mobile Ad Hoc Networks -- Secure and Verifiable Multi-owner Ranked-Keyword Search in Cloud Computing -- A Dynamic Differentiated QoS Based Call Admission Control Service Model for Core Node in Wireless Sensor Network Topology Control -- Secure and Privacy-Preserving Location Proof in Database-Driven Cognitive Radio Networks -- SDP: Separate Design Principle for Multichannel Scheduling in Priority-Aware Packet Collection -- On Computing Multi-agent Itinerary Planning in Distributed Wireless Sensor Networks -- FFDP: A Full-Load File Delivery Protocol in Satellite Network Communication -- Energy-Aware Clustering and Routing Scheme inWireless Sensor Network -- Serial Number Based Encryption and Its Application for Mobile Networks -- Fine-Grained Searchable Encryption over Encrypted Data in Multi-clouds -- Big-Little-Cell Based Handprint Positioning System -- Spectrum Sublet Game Among Secondary Users in Cognitive Radio Networks -- Delivering Content with Defined Priorities by Selective Agent and Relay Nodes in Content Centric Mobile Social Networks -- Rogue Access Point Detection in Vehicular Environments -- Information-Centric Resource Management for Air Pollution Monitoring with Multihop Cellular Network Architecture -- A Novel Location Privacy Mining Threat in Vehicular Internet Access Service -- iProtect: Detecting Physical Assault Using Smartphone -- Enhancing Wireless Security Against Reactive Jamming Attacks: A Game-Theoretical Framework -- A Quasi-Dynamic Inter-Satellite Link Reassignment Method for LEO Satellite Networks -- Domatic Partition in Homogeneous Wireless Sensor Networks -- High Performance DDDT-CWT Based Compressed Sensing Recovery of Images via Structured Sparsity -- Influential Spatial Facility Prediction over Dynamic Objects -- A Heuristic Stream Order Scheduling Algorithm for Intra-Superframe Power Management in WPANs -- Minimum-Latency Broadcast and Data Aggregation Scheduling in Secure Wireless Sensor Networks -- Data-Driven Privacy Analytics: A WeChat Case Study in Location-Based Social Networks -- A Double Pulse Control Strategy for Misinformation Propagation in Human Mobile Opportunistic Networks -- Efficient Line K-Coverage Algorithms in Mobile Sensor Network -- A Trust Evolution Mechanism for Mobile Social Networks Based on Wright-Fisher -- A Localized Channel Allocation Approach for Realtime Reliable and High Throughput Communication in Multi-channel Networks -- An Efficient and Secure Delegated Multi-authentication Protocol for Mobile Data Owners in Cloud -- Cooperative Spectrum and Infrastructure Leasing on TV Bands -- Information Security Enhancement with Actual Access Statuses of Users in the Multi-user System -- Joint Secure Beamforming and User Selection for Multi-user MISO Systems with Confidential Messages -- Network Reachability Analysis on Temporally Varying Interaction Networks -- Performance of Target Tracking in Radar Network System Under Deception Attack -- Resource Allocation in Cooperative Cognitive Maritime Wireless Mesh/Ad Hoc Networks: An Game Theory View -- Security and Privacy Issues of Fog Computing: A Survey -- Mobile Data Gathering with Time-Constraints inWireless Sensor Networks -- A Poisson Distribution Based Topology Control Algorithm for Wireless Sensor Networks Under SINR Model -- PPSSER: Privacy-Preserving Based Scheduling Scheme for Emergency Response in Medical Social Networks -- Secrecy-Oriented Adaptive Clustering Scheme in Device-to-Device Communications -- Cooperative Beamforming and Artificial Noise Design for Secure Multi-pair Communications in Wireless Two-Way Relay Networks -- On the Stable Throughput in Wireless LANs -- Antenna Selection in Large-Scale Multiple Antenna Systems -- Energy-Balanced Backpressure Routing for Stochastic Energy Harvesting WSNs -- Motion Recognition by Using a Stacked Autoencoder-Based Deep Learning Algorithm with Smart Phones -- SDN-Based Routing for Efficient Message Propagation in VANET -- Critical Point Aware Data Acquisition Algorithm in Sensor Networks -- Constructing Virtual Backbone with Bounded Diameters in Cognitive Radio Networks -- A Simplified Attack-Defense Game Model for NSSA -- Hadoop-Based Analysis for Large-Scale Click-Through Patterns in 4G Network -- Detecting Targets Based on a Realistic Detection and Decision Model in Wireless Sensor Networks -- Ant Colony-Based Energy Control Routing Protocol for Mobile Ad Hoc Networks.
Keywords: Computer software; Computer Communication Networks; Computer system performance; Information Systems; Algorithm Analysis and Problem Complexity; Computer Communication Networks; Information Systems Applications (incl. Internet).; System Performance and Evaluation; Management of Computing and Information Systems